AB1236 IMPROVING CLINICAL OUTCOME AND REDUCING COST FOR PATIENTS WITH RHEUMATIC DISEASES VIA ONLINE INTERACTION WITH RHEUMATOLOGISTS BASED ON SMART SYSTEM OF DISEASE MANAGEMENT (SSDM) MOBILE TOOL. (June 2019) - Wang, Yong; Luo, Li; Li, Qin; Wang, Fen; Huang, Anbin; Zhang, Hong; Ji, Peng; Zhao, Yanping; Shen, Lingxun; Wang, Zhengang; Wei, Feng; Xiao, Hui; et al.
Abstract : Background: Without efficient primary medical care and follow-up system in China, patients can choose any hospitals or doctors they like in seeking care. As a result, most patients rush to large hospitals. Once patients left those clinics, no follow up data is available. Surveys show that over 40% of the rheumatic patients don't need to go to a hospital, only need advice from rheumatologists. SSDM is a series of applications for chronic diseases management, which strengthens the interaction between doctors and patients based on valuable clinical data. Our previous study showed that patients can master the SSDM and perform self-management after training, including evaluations on disease activity and health assessment questionnaire (HAQ), as well as medication and lab test data entries. Objectives: To evaluate the feasibility and benefit of improving medical economics and disease activity outcomes in rheumatic patients through online consultation based on SSDM by rheumatologist. Methods: The rheumatologists implemented the education and training programs on patients in using SSDM and assist the patients in downloading the SSDM mobile application. The SSDM includes doctors' and patients' interfaces. The patients' terminal includes serial self-assessments (DAS28, SLEDAI, HAQ), medication management, adverse events management and lab records. After data entry, data synchronizes to the mobile of the authorized doctor. On the basis of these data, the rheumatologists can accept the request from their follow-up patients and practice consultation through SSDM in the form of text or voice. Results: From Feb 2015 to Jan 2019, 679 rheumatologists supplied 7, 405 patients (RA 35%, SLE 23%, AS 9.5%, gout 8.8%, Sjogren syndrome 3.8%, OA 3.4% and other 16.5%) with 10, 527 consultations. The consulting fee ranged from RMB 0 to 500 yuan (USD: RMB =1: 6.81) each in average of 78.10 ± 45.12 yuan, which match the registration fee in hospital. The total fee for consultations was 822, 169 yuan RMB. 37% patients receiving online consultation lived in different cities from the rheumatologists. If the patients seek medical care in hospital, in addition to the registration fees and medical expenses, the mean cost of transportation, accommodation, and lost wages was 577.48 ± 505.21 (200 - 2, 800) yuan. The total of cost for all patients would have been 6, 079, 135.00 yuan RMB, which is 7.39 times more compared with the cost of online. Among 2, 611 RA and 1, 671 SLE patients with repeat self-evaluations who were followed up for over 90 days, the treat-to-target rate improved from 28% to 45% (DAS28<=3.2) and from 41% to 70% (SLEDAI<=4), respectively. Survey shows that satisfaction rate with the consultations is 100%. Conclusion: Through online disease management and consultations using SSDM, Chinese patients with rheumatic diseases enjoy good quality of care at lower cost with high satisfaction. Armed with data science, SSDM may supply the rest world with an option for reshaping the healthcare system. Disclosure of Interests: None declared